Eksplorasi Tagading terhadap Konsep Bagun Ruang - Lamsoan Ritonga; Mangoloi P Siregar; Elda Kertiasa Sihombing; Roberto Tua Silaen; Hardi Tambunan; Ruth M Simanjuntak (Departement of Mathematics Education, 2023)
ABSTRACT This study aims to explore the relationship between the traditional musical instrument of the Toba Batak tribe known as Tagading and the concept of geometry. This study uses a qualitative approach through direct observation, interviews, and documentation to collect relevant data. The results of the study show that Tagading has geometric concepts in the form of geometric shapes and geometric shapes. The shape of the circle, as well as the structure and placement of the wood in Tagading illustrate these geometric concepts. Apart from that, the rhythmic patterns and long proportions of wood in Tagading also illustrate the relationship between music and mathematics. This research has important implications in developing mathematics learning methods that are relevant to local culture, as well as providing innovative learning experiences for students. The findings of this study can enrich our understanding of the relationship between culture, traditional music and geometric concepts.